PENGARUH KEAKTIFAN BELAJAR & KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR MAHASISWA - Nely Hartika; Farach Mariana (FKIP, Universitas Banten Jaya, 2019)
The purpose of this study was to determine 1) inflence of student learning activeness on learning achievement. 2) influence of emotional intelligence on learning achievement. 3) the influence of learning activeness & emotional intelligence on learning achievement. This type of research is quantitative descriptive research. This study took place at the University of Banten Jaya, the Teaching and Education Faculty, majoring in Accounting. The population in this study were all students of the FKIP Accounting Education University of Banten Jaya, the population in this study were 84 students. Data collection techniques using questionnaire and docimentation techniques. The analysis technique used is multiple linear regression analysis. Test of the significance of multiple linear regression (Test F) and test the significance of multiple linear regression coefficients (t test), in addition to the calculation of relative donations and effective contributions. The results showed that 1) Learning activity did not have a significant influence on the learning achievement of Accounting Education students of Banten Jaya Faculty of Teacher Training and Education which was indicated by table> thitung (1,667> 0,858). 2) Emotional Intelligence does not have a significant influence on the learning achievement of Accounting Education students of Banten Jaya Faculty of Teacher Training and Education which is indicated by table> thitung (1.667> 0.61) 3) Learning activity and intelligence together do not significantly influence the learning achievement of FKIP Accounting education students Banten Jaya University. Based on the F test, it is known that H0 received by Ha is rejected because Fcount> Ftable (0.594> 0.311) and the significance of significance of 0.05. That is 0.555. 4) Student learning activeness variables contribute 6.25% effectively, students emotional intelligence variable contributes 6.1% effectively so the total contribution is 12.35%, while the remaining 87.65% is influenced by other variables not examined.